Nano MnO2 immobilized covalently cross-linked chitosan and PVA based highly flexible membranes. (17th May 2019) - Yar, Muhammad; Masood, Aneeqa; Batool, Razia; Shahzadi, Lubna; Khan, Ather Farooq; Yousaf, Zunaira; Rafique, M Yasir; Razaq, Aamir
Abstract: In era of modern disposable and bendable energy storage technology, flexible and environmentally safe electrodes are extremely feasible. This study elaborates the synthesis of highly flexible and stretchable polymer gel membrane by covalently cross linking of chitosan (CS) and poly vinyl alcohol (PVA) immobilized MnO2 for efficient, light-weight and cost-effective energy storage technologies. Fourier transform infrared spectroscopy (FTIR) revealed the existence of CS/PVA as well as MnO2 in original form without any chemical change. 3-dimensional morphology including porosity of the presented fabricated membranes are examined by scanning electron microscopy (SEM). Presented CS/PVA based MnO2 membranes were bendable and can be cut in any shape by the simple usage of scissor to employ by means of working electrode. Furthermore, electrochemical behaviour was tested by cyclic voltammetry (CV) and Galvanostatic charge/discharge (GCD) measurements in neutral/acidic electrolytes. CS/PVA based MnO2 membranes showed excellent capacitive behaviour with specific capacitance of ~140 F g −1 . GCD measurements also verified efficient kinetics of charging/discharging at low and high current rates as curves were symmetric. Presented flexible and electroactive CS/PVA based MnO2 membranes will be highly suitable candidates for bendable electrode material in modern high-tech flexible energy storage devices.